Die protestantischen »Sekten« und der Geist des (Anti-)Imperialismus: Religiöse Verflechtungen in den Amerikas - Schäfer, Heinrich Wilhelm (transcript, 2020)
Religious entanglements in the Americas are increasingly becoming a political issue. This essay takes a critical look at it.